Un programme de formation à l’élaboration et à l’évalutation de prgrammes visant à favoriser l’inserting socio-professionnelle des jeunes - Monette, Marcel (Canadian Journal of Counselling and Psychotherapy, 2011)
Guidance counsellors in Quebec recognize the importance of developing skills for program elaboration and evaluation. To develop these skills, a training model is proposed. The model used is both systematic and systemic. On the one hand, it teaches the behaviours and cognitive abilities required to elaborate and evaluate intervention programs. On the other hand, it goes further than the simple acquisition of skills. It deals with the transfer of on-the-job training and the impact of counsellor intervention on their clients and on their organization.